The Effect of Discovery Learning Model on Improving Students’ Motivation and Learning Outcomes in Class X on Chemical Bonding Material - Aulia Zahra Hutasuhut; Eva Marlina Ginting; Paul Andohar Sipayung (Universitas Lampung, 2025)
The Effect Of Discovery Learning Model On Improving Student’s Motivation and Learning Outcomes In Class X On Chemical Bonding Material. This study aims to determine the influence of the discovery learning model on increasing student motivation and learning outcomes in chemical bonding material. This study was conducted at SMA Swasta Gelora Pancasila Pegajahan, Pegajahan District, Serdang Bedagai Regency. The sample used was students of class X-2 as the experimental class or group and class X-1 as the control class. The instrument used in this study was a test instrument in the form of a multiple-choice objective test to see student learning outcomes obtained through a posttest and a questionnaire in the form of a statement to see student learning motivation. The results of the study showed that there was an influence of the discovery learning model on increasing student motivation and learning outcomes in chemical bonding material. This can be seen from the results of the posttest hypothesis test using the t-test obtained that tcount> ttable = 5.77> 1.671. The results of student learning motivation using the t-test obtained that tcount> ttable = 2.26> 1.671. The relationship between motivation and student learning outcomes shows that the correlation is 0.861 (very high correlation).